2010
DOI: 10.1094/mpmi-23-8-1053
|View full text |Cite
|
Sign up to set email alerts
|

The Basic Leucine Zipper Transcription Factor Moatf1 Mediates Oxidative Stress Responses and Is Necessary for Full Virulence of the Rice Blast Fungus Magnaporthe oryzae

Abstract: Magnaporthe oryzae is the causal agent of rice blast disease, leading to enormous losses of rice production. Here, we characterized a basic leucine zipper (bZIP) transcription factor, Moatf1, in M. oryzae, a homolog of Schizosaccharomyces pombe ATF/CREB that regulates the oxidative stress response. Moatf1 deletion caused retarded vegetative growth of mycelia, and the Moatf1 mutant exhibited higher sensitivity to hydrogen peroxide (H(2)O(2)) than did the wild-type strain. The mutant showed severely reduced acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
165
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(172 citation statements)
references
References 82 publications
5
165
1
1
Order By: Relevance
“…The impairment in the growth of invasive hyphae, therefore, can be attributed to ROS accumulation within plant cells due to the absence of Alg3. In addition to the Dslp1 and Dalg3 mutants, several other M. oryzae mutants have been reported to induce ROS accumulation in penetrated plant cells, including mutants disrupted in DES1 (Chi et al, 2009), ATF1 (Guo et al, 2010), AP1 (Guo et al, 2011), HYR1 (Huang et al, 2011), CHS6 , and CRC1 genes. DES1, AP1, ATF1, and HYR may be involved in ROS detoxification, because expression levels of ROS-detoxifying genes were significantly reduced in these mutants (Chi et al, 2009;Guo et al, 2010Guo et al, , 2011Huang et al, 2011;Adam et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The impairment in the growth of invasive hyphae, therefore, can be attributed to ROS accumulation within plant cells due to the absence of Alg3. In addition to the Dslp1 and Dalg3 mutants, several other M. oryzae mutants have been reported to induce ROS accumulation in penetrated plant cells, including mutants disrupted in DES1 (Chi et al, 2009), ATF1 (Guo et al, 2010), AP1 (Guo et al, 2011), HYR1 (Huang et al, 2011), CHS6 , and CRC1 genes. DES1, AP1, ATF1, and HYR may be involved in ROS detoxification, because expression levels of ROS-detoxifying genes were significantly reduced in these mutants (Chi et al, 2009;Guo et al, 2010Guo et al, , 2011Huang et al, 2011;Adam et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…They consist in non-fluorescent molecules that become fluorescent when oxidised by ROS, and the emitted fluorescence can be observed by fluorimetry and/or by fluorescent microscopy, an advantage of such probes (Benikhlef et al, 2013;Bulgakov et al, 2012;Fester and Hause, 2005;Guo et al, 2010;Kolla et al, 2007;L'Haridon et al, 2011;Li et al, 2007;Liu et al, 2010;Ma et al, 2013;Peleg-Grossman et al, 2012;Plancot et al, 2013;Tada et al, 2004;Wen et al, 2008;Ye et al, 2013). Luminol or luminol analogues are sensitive chemiluminescent probes used to quantify a relative intensity of ROS by counting the emitted light with a luminometer, CDD camera or a scintillation counter (Dubreuil-Maurizi et al, 2010;Flury et al, 2013;Kunz et al, 2006;L'Haridon et al, 2011;Mersmann et al, 2010).…”
Section: Detection Of Rosmentioning
confidence: 99%
“…Recently, the transcription factor Moatf1 homologous to the yeast ATF/CREB that regulates the oxidative stress response was identified in Magnaporthe grisea. Targeted gene deletion of Moatf results in a higher sensitivity to ROS, a reduced expression and activity of extracellular laccases and peroxidases associated with a reduced virulence on rice (Guo et al, 2010). H 2 O 2 accumulated around the appressorium in the deletion mutant but not in the wild type fungus and inhibition of the rice NADPH oxidases with diphenyleneiodonium (DPI) restored hyphal growth and virulence of the mutant (Guo et al, 2010).…”
Section: The Multiple Functions Of Rosmentioning
confidence: 99%
See 1 more Smart Citation
“…Different bZIP-type TFs have also been characterized in various filamentous fungal species, including Aspergillus nidulans (7,8), Neurospora crassa (9), and the plant pathogens Fusarium graminearum (10 -12) and Magnaporthe oryzae (13)(14)(15). Deletions and functional characterizations of these genes revealed that bZIP-type TFs are involved in mediating fungal development, sexuality, stress responses, secondary metabolisms, and especially the virulence of plant pathogens.…”
mentioning
confidence: 99%